Negligence and illegality - Erbacher, Sharon (Hart studies in private law ;, 2017)
This book examines claims in negligence arising from illegal conduct of the claimant. The book argues that the only circumstance where illegality doctrine should be applied to deny a claim is where this is necessary to preserve the coherence of the legal system. It also contains a detailed study on the scope of the coherence rationale and the principles that will determine its application.